3. THE RESULT OF LOOP STITCHING THE CERVIX AT NGHE AN OBSTETRICS AND PEDIATRICS HOSPITAL (Vietnam Journal of Community Medicine, 2023)
Objectives: To evaluate the results of loop stitching the cervix to prevent miscarriages and prematurebirths at Nghe An Obstetrics and Pediatrics Hospital. Methods: Cross-sectional description of allpatients who underwent loop stitching of the cervix at Nghe An Obstetrics and Pediatrics Hospital.Result: Mainly, pregnant women were stitched at 12-15 weeks (63.8%). The mean age of the fetuswas 15.2±2.7 weeks. 94.2% of pregnant women had no complications: infection or miscarriage in 3days after stitches. The neonatal survival rate was 94.2%. Full-term birth has 58 cases, accountingfor 84.1%. Miscarriage and highly premature birth under 28 weeks is 4.3%. Normal birth accountsfor a high rate of 85.5%. There were no cases of surgical intervention. Conclusions: The method ofloop stitching the cervix is safe, suitable for many conditions of pregnancy, and helps to improve theoutcome of a pregnancy.
Keywords: Loop stitching the cervix.